Big data - the new challenge facing business - Tashkova, M. (Економічний вісник Донбасу, 2016)
Today there are many sources that create large volumes of data. On the one hand, these are the people themselves, who are able to generate information on their own using the Internet and social networks. On the other hand, with the advent of the Internet of Things it is not only users that generate information, but also most of the devices that are used daily. The power of big data technologies involves working and making business decisions using the maximum amount of data. The more data, the more substantiated analyses and forecasts. The challenge now is - what technologies these large volumes of data could be managed with.